Does soil type hold a role in the dynamic of carbon dioxide (CO2) emission from paddy rice fields?. Issue 1 (April 2021) - Ariani, M; Hanudin, E; Haryono, E
Abstract: Soil holds a vital role in forming greenhouse gas (GHG) emission from paddy rice fields. There are three main GHG from paddy rice, namely Methane (CH4 ), nitrous oxide (N2 O) and carbon dioxide (CO2 ). This research aimed solely to explore the dynamic of CO2 emission from paddy rice with different soil types, namely sandy loam and clay soil. In each site, two-factor treatments were applied. There was water regime namely 1) continuously flooded, and 2) alternate wetting-drying (AWD) as the first factor and organic matter application namely 1) without organic matter (OM), 2) bio-compost 5 t ha -1, and 3) bio-compost 10 t ha -1 . Carbon dioxide flux in sandy loam soil ranged between -11.50 to -0.47 mg CO2 m -2 d -1 under continuously flooded conditions and -7.64 to 3.03 mg CO2 m -2 d -1 alternate wetting-drying conditions. The clay soil was lower, ranging between -7.43 to 0.51 mg CO2 m -2 d -1 under continuously flooded conditions and -5.54 to 0.47 mg CO2 m -2 d -1 under alternate wetting-drying conditions. Clay soil tended to emit less CO2 emission than sandy soil. The result showed that soil physical characteristic plays an important role in controlling CO2 from paddy rice.